Ticket Purchase System using RFID and Bus Location Tracking System with GPS Tracker - Nur Izzatul Aliss Ab Rashid; Nor Aida Akma Alias; Nur Masziana Muhammad Soffian; Hannes Masandig (Multidisciplinary Applied Research and Innovation, 2023)
Ticket Purchase System Using RFID And Bus Location Tracking Systems With GPS Tracker is a system that performs ticket bookings and bus location tracking, developed for intercity Malaysia bus operators. The technology employs Radio Frequency Identification (RFID), which allows the cardholder to perform a transaction with RFID card in a contactless payment terminal such as a kiosk. The system aims to help user book bus tickets online and make payments using RFID technology, by scanning RFID card at ticketing kiosks counter. In addition, the implementation of a GPS tracker for the current location of the bus so that users can know where they are while boarding the bus. We also want to generate notifications to passengers as well as establish an expected arrival time for the trip so that they can be aware of the arrival of the bus. The methodology that has been used to develop this system is the System Development Life Cycle (SDLC) Waterfall Model and internet of things (IoT) equipment, for example, Raspberry Pi 3, RFID Scanner Card Module, and GPS Board Module. It has also been tested several times and got satisfactory results. The result of the evaluation of the respondents’ opinions about this system is that most respondents, namely 8/10 people, stated that this system facilitates the purchase of tickets online while 8/10 respondents think that there is an increase in their bus company’s ticket sales by 60% and above compared to before using this system. Hence, our future improvement goal is to integrate NFC in the payment system.